Logframe Model as analytical tool for the Brazilian Breastfeeding and Feeding Strategy - Santos TAVARES, Josivânia; de Souza VIEIRA, Daniele; Kiev Carvalho DIAS, Tayanne; Grubisich Mendes TACLA, Mauren Teresa; COLLET, Neusa; Pereira da Silva REICHERT, Altamira (Revista de Nutrição, 2023)
Objective This study aimed to analyze the implementation of the Brazilian Breastfeeding and Feeding Strategy in a Brazilian northeast capital. Methods This exploratory research uses a qualitative approach that was served with five tutors and three managers related to the strategy. The approach elaborated a graphic representation of the problem tree of the Brazilian Breastfeeding and Feeding Strategy, and subsequently, a diagram with the strategy structure was developed per the components of Logframe model. Results The study identified weaknesses on the information shown in official documents from this strategy as well as principal issues in the implementation. Using the Logframe Model, the research proposed actions to modify this reality. Conclusion The Logframe Model is an important management instrument that can contribute to strengthening and expanding the Brazilian Breastfeeding and Feeding Strategy. Therefore, it can increase breastfeeding and healthy complementary feeding rates to reduce infant mortality and morbidity.